SECUIL KONTROVERSI KITAB BIDĀYATUL HIDĀYAH KARYA AL-GHAZĀLIY (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
Study of Prophet Muhammad’s tradition (sunnah) can not be quit of the research to all of his companies and the men ater. They represent agent conveyor of the sunnah, that is everything that concerning with the word of utterance qawl deed of the actifity fi’il and confession of the silent, taqrîr without Prophet comment of Saw. In consequence, research to all of the people and the shahâbah after have very importent meaning in course of forwarding of an the hadith. This matter silver its bearing with conseervancy of very irrespective hadith otenticity of sincerity and mainstay of dhabith of duracy of them in submitting an hadith.